Experimental Study on Explosion Pressure and Rock Breaking Characteristics under Liquid Carbon Dioxide Blasting. (27th August 2018) - Zhang, Yanan; Deng, Junren; Ke, Bo; Deng, Hongwei; Li, Jielin
Abstract : A liquid carbon dioxide blasting experiment was carried out under free field conditions, alongside a liquid carbon dioxide rock breaking experiment, to investigate explosion pressure variation and rock breaking characteristics under liquid carbon dioxide blasting. The experimental results show that the internal and external explosion pressures of the liquid carbon dioxide fracturing devices all rapidly increased at first, before attenuating vibrantly after blasting. When the explosion pressure was raised, the internal explosion pressure increased first exponentially and then linearly, while the external explosion pressure increased exponentially throughout. The duration time of the blasting effect stage was about 45 ms. Under the combined effect of jet impingement and a gas wedge of high-pressure carbon dioxide, the rock is subjected to tensile failure. The impact failure and the "gas wedge effect" of high-pressure carbon dioxide play a key role in the rock breaking of liquid carbon dioxide blasting technology.